A Study on Utility of Industrial Training of Polytechnic Teachers - Jain, P. C.; Gupta, B. L. (Journal of Engineering Education Transformations, 1993)
The knowledge in Science and Technology is advancing at an accelerating rate. This has changed the Indian Industrial Scene and it is ever changing. Present passouts from technician education system are unable to cope up with the changing requirements of the industries.